Bodily arousal differentially impacts stimulus processing and memory: Norepinephrine in interoception. (2016) - Critchley, Hugo D.; Garfinkel, Sarah N.
Abstract: Bodily arousal modulates stimulus processing and memory, contributing to expression of emotional salience. The "glutamate amplifies noradrenergic effects" (GANE) model proposed by Mather and colleagues can be extended to account for the differential impact of interoceptive (notably cardiac afferent) signals on sensory processing. However, some emotion-specific effects, for example, for fear, may further depend on functional anatomical organisation of affect-related brain structures.